Exploring the therapeutic potential of xanthones in diabetes management: Current insights and future directions - Riya Saikia; Kalyani Pathak; Pallab Pramanik; Md Ariful Islam; Shreyasi Karmakar; Saptasikha Gogoi; Manash Pratim Pathak; Dibyajyoti Das; Jon Jyoti Sahariah; Mohammad Zaki Ahmad; Aparoop Das (Elsevier, 2024)
The search for effective antidiabetic agents, both synthetic and natural, has intensified over the years. This review provides a comprehensive examination of xanthone compounds as potential antidiabetic agents, exploring their sources, chemical structures, and pharmacological properties. Xanthones have been shown to enhance insulin sensitivity, modulate glucose metabolism, and mitigate oxidative stress and inflammation through various mechanisms. Key molecular targets include AMP-activated protein kinase (AMPK), peroxisome proliferator-activated receptors (PPARs), α-amylase, and α-glucosidase.The review details in vitro studies demonstrating that xanthones like γ-mangostin and mangiferin inhibit α-amylase and α-glucosidase with IC50 values of 3.2 μM and 5.6 μM, respectively, highlighting their potential to improve glucose metabolism. In vivo studies have shown that xanthones improve glucose homeostasis, lipid profiles, and overall glycemic control in diabetic models. For instance, mangiferin administration in streptozotocin-induced diabetic rats resulted in lower fasting blood glucose levels and improved HDL levels.Moreover, the safety profile and potential side effects associated with xanthone usage are discussed, providing a balanced view of their therapeutic potential. This review consolidates current knowledge on xanthones' antidiabetic properties and serves as a valuable resource for further research and development of these compounds as antidiabetic agents.